Scaffolding Based Learning: Strategies For Developing Reflective Thinking Skills (A Case Study On Random Variable Material in Mathematics Statistics Courses) - Hidayatul Khusna, Arif (Journal of physics. Conference series, 2021)
Scaffolding is a learning model by providing assistance based on student difficulties. The purpose of this study is to describe the application of scaffolding-based learning to support students’ reflective thinking skills in mathematics statistics courses. Research subjects were 43 5th semester students of mathematics education study programs. This type of research is a qualitative descriptive study with three research procedures carried out, namely: 1) a preliminary study, 2) planning, and 3) implementation. The instruments used were lecturer activity observation sheets and student activity observation sheets. The results showed that the components of scaffolding-based learning can be used to support students’ reflective thinking skills in this case in learning mathematics statistics. Explaining and reviewing play a role in shaping pre-reflective situations, restructuring in shaping reflective situations, and developing conceptual thinking play a role in shaping post-reflective situations.